NON-OBSERVED ECONOMY AS A PART OF THE DEVELOPING ECONOMY - T.K.Bekzhanova,; A.B.Temirova, (Academic Journal of Physical and Chemical Sciences, 2019)
This article examines the features of the unobserved economy, which requires improvement by market institutions and formal legal acts. Having limitations reduces the opportunities for effective use of resources in this area. The scale of the non-observed economy in many respects testifies to the degree of the formation of market instruments in Kazakhstan and the CIS countries. As is known, the non-observed economy includes informal, hidden (shadow) and illegal (illegal) production activities. Improvement of institutional reforms will allow to create an unobserved economy and include it in a single economic turnover, which will allow economic growth and social transformations in the country.